Age-related circadian rhythm and variability of large- and small-airway function in healthy non-smoking adults: Data from 7-day diurnal and nocturnal home monitoring using an electronic portable spirometer - Zhang, Xue; Zhang, Yingying; Zhou, Yan; Yin, Dongning; Lv, Chengjian; Lin, Jinwang; Bao, Wuping; Zhang, Min (Frontiers in Public Health, 2022)
Background The aim of the study was to investigate the possible influencing factors of the large- and small-airway function variation in healthy non-smoking adults. Methods Healthy non-medical non-smoking adults were enrolled in this prospective cohort study. Each participant took the portable spirometer test relying only on video teaching. Then conventional spirometry and bronchodilation test were conducted using a Jaeger spirometer, followed by 7-day diurnal and nocturnal home monitoring using a portable spirometer. Results A drop in both large- and small-airway function began at about 25 years of age, and a rapidly decline at about 50 years. The CV of FEV1 (r = 0.47, P = 0.0082) and small-airway function variables correlated with age (r ≥ 0.37, P < 0.05 for both MEFs and MEFs/FVC), especially for evening small-airway function variables. The CV of large (4.666 ± 1.946, P = 0.002 for FEV1; 4.565 ± 2.478, P = 0.017 for FEV3) and small airways (10.38 ± 3.196, P = 0.031 for MEF50 and 11.21 ± 4.178, P = 0.023 for MMEF) was higher in the 45- to 60-year subgroup than in the 30- to 45-year and 18- to 30-year subgroups. Interpretation Age was the main influencing factor of both central and peripheral airway function variability, especially for the small-airway function in the evening. The LLN of small-airway variables varies depending on the age and circadian rhythm. People older than 45 years should pay more attention to monitoring small-airway function in the evening, which will be helpful for early clinical detection of those at high risk for asthma. Trial registration number ChiCTR2100050355.